Decisional Quality of Women Choosing a Contraceptive Method in an Urban Gynecology Practice [8O]. (May 2016) - Sridhar, Aparna; Lambrechts, Sylvia; Munnangi, Meghana; Kwan, Lorna; Saigal, Christopher
Abstract : INTRODUCTION: Women have an array of birth control options to choose from. Little is known about the decisional quality of choices made in reproductive health. METHODS: A cross-sectional survey of women in a high-volume Obstetrics/Gynecology clinic was conducted. Eligible participants were English speaking women of reproductive age that completed a discussion with their provider regarding contraceptive options. Familiarity for contraceptive options was measured using a 5-point Likert scale; Decisional conflict was measured using the SURE (4-item) validated scale. Questionnaire content also included items for satisfaction with care, shared decision making, and health literacy. RESULTS: Participants (N=105) were most familiar with condoms (97%) and the birth control pill (96%), and were least familiar with tubal ligation (36%) and the sponge (34%). Most women chose the birth control pill (44%) as their contraceptive choice. Women with low decisional conflict (84%; SURE=4), stated that they were more likely to stick to their decision (90% versus 73%), and were more satisfied with their decision (98% versus 50%). Those satisfied with their decision were more likely to be younger, not employed full-time (40% versus 69%), more likely to have made a choice of method both before (91% versus 69%) and after seeing the doctor (98% versus 54%), and had lower decisional conflict. CONCLUSION: Increased decisional conflict is associated with lower patient satisfaction and a lowered patient predicted adherence to birth control strategy. Methods to improve decisional conflict, such as shared decision making, may improve decision quality for women choosing from various contraceptive methods.